2020
DOI: 10.3390/su12051773
|View full text |Cite
|
Sign up to set email alerts
|

Temporal–Spatial Distribution of Ecosystem Health and Its Response to Human Interference Based on Different Terrain Gradients: A Case Study in Gannan, China

Abstract: The exploitation, utilization, and protection of land resources are some of the great social problems during the process of rapid urbanization in China. The status of land use directly affects ecosystem health (ESH). The evaluation of ESH and the spatial correlations between urbanization caused by human interference help us to analyze the influence of urbanization on ecosystems and also provide new insight into reasonable and scientific resource management. In this study, we evaluated the ESH of Gannan, in Jia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, the northern part of the property zone exhibited a decline in ecosystem health in 2011, and the declined areas were distributed in the restricted and exhibition zones within the property zone. A possible explanation is that those areas are close to Bayanbulak town and vulnerable to tourism and grazing activities, which would decrease the ecosystem health [75]. Jia et al (2011) and Qian et al (2016) also found the low ecosystem health level areas were easier to be affected by human activities in Sanjiangyuan and Dongting Lake wetland, respectively [41,76].…”
Section: Ecosystem Health Assessmentmentioning
confidence: 99%
“…However, the northern part of the property zone exhibited a decline in ecosystem health in 2011, and the declined areas were distributed in the restricted and exhibition zones within the property zone. A possible explanation is that those areas are close to Bayanbulak town and vulnerable to tourism and grazing activities, which would decrease the ecosystem health [75]. Jia et al (2011) and Qian et al (2016) also found the low ecosystem health level areas were easier to be affected by human activities in Sanjiangyuan and Dongting Lake wetland, respectively [41,76].…”
Section: Ecosystem Health Assessmentmentioning
confidence: 99%
“…Through the investigation focusing on different ecosystem types on all levels of TGs, we found that the distribution of Shannan’s ecosystem types is significantly different in different TGs, mainly forest and grassland, and the areas of these two types increased at all TGs. The area of farmland decreases with the increase in the TGs; it reduced mainly at the third, fourth and fifth TGs, probably due to its higher elevation and slope restricting the development of agriculture [ 48 ]. The decreases in forest area are found with TGs increasing, which is different from the previous study concerning low-altitude regions, including Anhui province, Gannan region in Jiangxi province and Huailai County in Hebei province.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the space association and agglomeration model between ecosystem service value and urbanization in Shannan, we conducted a spatial correlation analysis. Moran’s I index shows the spatial association put forward by Moran (1950), which shows the similarity of the spatially adjoining regional unit value [ 48 ]. This research explored the spatial association with global bivariate Moran’s I index and local bivariate Moran’s I index in Geo Da spatial analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…In order to better reflect the distribution pattern of LER on different terrain gradients, we merged the DEM and slope in the ArcGIS10.7 software to establish the terrain niche index (TNI) [ 31 ] ( Figure 2 ). As a comprehensive terrain factor, it can make up for the non-obvious changes in low terrain gradient caused by high elevation, small slope, or low elevation and large slope, and effectively reflect the spatial differentiation of terrain gradient [ 43 ]. The calculation [ 31 ] is as follows: where TNI represents the terrain niche index; and , respectively, represent the altitude value of any point and its average altitude value around the neighborhood in the research around; and are the slope value of any point and its average slope value around the neighborhood in the study area, respectively.…”
Section: Methodsmentioning
confidence: 99%